Economic crisis, social networks, and political preferences - Liu, L; Kuo, A; Fernandez-Albertos, J (Oxford University Press, 2020)
How did the great recession affect policy and partisan preferences in the most afflicted countries? We theorize the role of a previously under-emphasized source of preferences: the size and scope of one’s exposure to other individuals who have been exposed to the crisis. Contact with others who have economically suffered should be an additional channel for the crisis’ effects on policy preferences. We gathered data during the recession from a crisis-hit country, Spain, to measure the size of the respondent’s social networks in different ways and the impact of the crisis upon them. We also measured a battery of policy and political preferences (support for austerity, the euro, supranational institutions and new parties). We find strong associations between support for anti-status quo policies and anti-establishment parties and exposure to economic suffering within one’s social networks in ways that enrich our understanding of the process of preference formation in times of crisis.